Analysis Influence Growth Economy, Level Wages Minimum and Level Education to Unemployment in Pamekasan Regency - Rohani, Alya; Imaningsih, Niniek (Journal of Regional Economics and Development, 2025)
This study aims to determine the effect of economic growth, minimum wage levels, and education levels on the unemployment rate in Pamekasan Regency in the period 2014–2023. The background of the study is based on the problem of unemployment which remains a significant issue in regional development, where high unemployment is related to fluctuations in economic growth, minimum wage policies, and low educational attainment of the community. This study uses a quantitative method with multiple linear regression analysis, while research data was obtained from the Central Statistics Agency (BPS) of Pamekasan Regency. The results show that economic growth has a negative effect on unemployment, so that economic improvement can reduce the number of unemployed. The minimum wage variable has a positive effect, which means that wage increases tend to increase unemployment due to limited labor absorption capacity. Meanwhile, the level of education has a negative and significant effect, meaning that the higher the community's education, the lower the unemployment rate. Simultaneously, all three variables are proven to have a significant effect on unemployment in Pamekasan Regency.